Effects of caffeine supplementation on physical performance and mood dimensions in elite and trained-recreational athletes - Jodra, Pablo; Lago Rodríguez, Ángel; Sánchez Oliver, Antonio Jesús; López Samanes, Álvaro; Pérez López, Alberto; Veiga Herreros, Pablo; San Juan Ferrer, Alejandro; Rodríguez, Roberto (My University, 2020)
.

1. Background Caffeine supplementation (CAFF) has an established ergogenic effect on physical performance and the psychological response to exercise. However, few studies have compared the response to CAFF intake among athletes of different competition level. This study compares the acute effects of CAFF on anaerobic performance, mood and perceived effort in elite and moderately-trained recreational athletes. 2. Methods Participants for this randomized, controlled, crossover study were 8 elite athletes (in the senior boxing national team) and 10 trained-recreational athletes. Under two experimental conditions, CAFF supplementation (6 mg/kg) or placebo (PLAC), the athletes completed a Wingate test. Subjective exertion during the test was recorded as the rating of perceived exertion (RPE) both at the general level (RPEgeneral) and at the levels muscular (RPEmuscular) and cardiorespiratory (RPEcardio). Before the Wingate test, participants completed the questionnaires Profiles of Moods States (POMS) and Subjective Vitality Scale (SVS). 3. Results In response to CAFF intake, improvements were noted in Wpeak (11.22 ± 0.65 vs 10.70 ± 0.84; p = 0.003; 2 =0.44), Wavg (8.75 ± 0.55 vs 8.41 0.46; p = 0.001; 2 =0.53) and time taken to reach Wpeak (7.56 ± 1.58 vs 9.11 ± 1.53; p <  0.001; 2 =0.57) both in the elite and trained-recreational athletes. However, only the elite athletes showed significant increases in tension (+ 325%), vigor (+ 31%) and SVS (+ 28%) scores after the intake of CAFF compared to levels recorded under the condition PLAC (p <  0.05). Similarly, levels of vigor after consuming CAFF were significantly higher in the elite than the trained-recreational athletes (+ 5.8%). 4. Conclusions CAFF supplementation improved anaerobic performance in both the elite and recreational athletes. However, the ergogenic effect of CAFF on several mood dimensions and subjective vitality was greater in the elite athletes.
Artículos en revistas